Donor trends a resource book of development assistance in the Philippines. - Association of Foundations (Quezon City Association of Foundations Philippines, 2000)
It is a database of information on donor agencies. It is a sourcebook on fund sources that is valuable for many organizations grappling with problems of survival and sustainability.
A comprehensive donor database in the Philippines, which include information on programs, beneficiaries of programs and projects, location, and funding levels given by the different donors- bilateral, multilateral, international non- government organization, as well as local foundations. The database provides a short analysis on donors in and out of the Philippines giving readers background information in the fundings done in the past, typology of funding institutions, funding levels, funding priorities and beneficiaries, projections on the future of development assistance and top problems faced by donors working in the Philippines. The material also features annexes (definition of terms, classifications according to program area and nature of projects, eligibility requirements) which give useful information in understanding the database and providing additional useful information.
Jointly published with Caucus of Development NGO Networks.
Keywords: Endowments -- Philippines; Endowments -- Philippines -- Directories; Charitable uses, trusts, and foundations -- Philippines -- Directories